Analisis Varians Untuk Mengukur Efisiensi dan Efektifitas Anggaran Perusahaan PG Gempolkrep Tahun 2014 – 2015 - Budi Utami; Eny Setyariningsih (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
The budget functions as an aspect of planning and supervision in the company's operational activities. The budget must be able to adjust the plans made for various parts of the company, so that one activity plan will be in harmony with another. Efficiency is the relationship between goods and services produced by an activity and the resources used. An activity is said to be efficient if it is able to produce certain outputs with the lowest possible input or with certain inputs it is able to produce the maximum output (spending well). Meanwhile, effectiveness is the relationship between the output and the goals or objectives that must be achieved. Operational activities are said to be effective if the activity process achieves the final policy goals and objectives (spending wisely). The purpose of this study was to determine the variance of the sales and production budget of PG. Gempolkrep Mojokerto 2014 - 2015 and measures the level of efficiency and effectiveness of PG's sales and production budget. Gempolkrep Mojokerto 2014 - 2015. The analysis method used is analysis of variance. The results of this study contained unfavorable variances in the sales budget for 2014 and 2015. Production budgets for 2014 and 2015 showed favorable variances. The use of the budget for 2014 and 2015 is less than 80% or is in the efficient category. The company's budget performance for 2014 - 2015 is in the range of less than 80% or is in the less effective category.